(untitled) - Latham-Koenig, Christina (Oxford, 2012)
The English File third edition digital components help to make the most of teaching and learning opportunities inside and outside the classroom. The digital package includes: iTools (a digital classroom resource), iTutor and iChecker for students, Pronunciation App for mobiles, Online Workbook.
Keywords: Anh ngữ,English language; Dạy và học,Nói tiếng nước ngoài,Study and teaching,Foreign speakers